Life Cycle Assessment (LCA) of Industrial Milk Production. - Eide, Merete Hogaas (The International Journal of Life Cycle Assessment)
A Life Cycle Assessment (LCA) was carried out for milk production extending from the origin of the inputs to the agricultural step to the consumer phase and the waste management of the packaging. Three Norwegian dairies of different sizes and degree of automation were studied. The main objectives were to find any hot spots in the life cycle of milk, to determine the significance of the dairy size and degree of automation, and to study the influence of transport. The agriculture was found to be the main hot spot for almost all the environmental themes studied, although the dairy processing, packaging, consumer phase and waste management were also of importance. The consumer phaes was the main contributor to photo oxidant formation and important regarding eutrophication. The small dairy was found to have a greater environmental impact than the middle sized and the largest dairies. The transport did not have any major influence.